2021
DOI: 10.1149/1945-7111/ac4129
|View full text |Cite
|
Sign up to set email alerts
|

Methods—On the Reliability of the Electrochemical Data Recorded on Nickel Foam in Alkaline Solution: The Illusive Surface Oxide Layer

Abstract: The extensive application of nickel foam (Ni foam) as current collector in supercapacitors has raised caveats on the contribution of the redox-active Ni foam to the measured capacities. However, due to the overlooked qualitative features (i.e., shapes) of the cyclic voltammograms (CVs), the redox reaction of the Ni foam oxide layer (NiFOL) has been frequently confused with the true electrochemical signature of the coated materials in alkaline solution. Herein, experimental CVs, scanning electron microscopy ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The first oxidation peak is classified as Ni­(0–II) (−0.2–0.15 V vs Ag/AgCl), and the current density of the second oxidation peak (0.35–0.55 V vs Ag/AgCl) is lower than that of the first CV curve, demonstrating that the low-valence species on the surface of Ni­(OH) 2 gradually transform to NiOOH species (Figure S6d). , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first oxidation peak is classified as Ni­(0–II) (−0.2–0.15 V vs Ag/AgCl), and the current density of the second oxidation peak (0.35–0.55 V vs Ag/AgCl) is lower than that of the first CV curve, demonstrating that the low-valence species on the surface of Ni­(OH) 2 gradually transform to NiOOH species (Figure S6d). , …”
Section: Resultsmentioning
confidence: 99%
“…The first oxidation peak is classified as Ni(0− II) (−0.2−0.15 V vs Ag/AgCl), and the current density of the second oxidation peak (0.35−0.55 V vs Ag/AgCl) is lower than that of the first CV curve, demonstrating that the lowvalence species on the surface of Ni(OH) 2 gradually transform to NiOOH species (Figure S6d). 41,43 As can be seen from Figure 3a, the first CV curve of 14%Ce-Ni(OH) 2 contains two oxidation peaks, corresponding to Ni(0−II) (−0.2−0.15 V vs Ag/AgCl) and Ni(II−III) (0.35− 0.6 V vs Ag/AgCl). 44 In the second CV curve, the extra oxidation peak may belong to hydrogen desorption at −0.45 V vs Ag/AgCl (Figure 3b).…”
Section: Structure and Morphology Characterizationmentioning
confidence: 96%
“…In comparison to LaCaCoCrO 6 , the specific capacitance of nickel foil used is almost negligible. [ 64 ] Therefore, the influence of Ni foil on electrode performance might be neglected.…”
Section: Resultsmentioning
confidence: 99%
“…However, recently, many studies revealed the electrocatalytic activity of Ni foam toward OER and HER as it develops a passive oxide layer on the surface once immersed in the electrolyte. This oxide layer might lead to interference with the recorded electrochemical activity of the actual catalyst, leading to misleading results . To this end, Ti mesh, as a low cost material ($.23/inch), was proven to be a suitable substrate due to its large-surface area, high stability in different pH values, and high corrosion resistance .…”
Section: Introductionmentioning
confidence: 99%
“…This oxide layer might lead to interference with the recorded electrochemical activity of the actual catalyst, leading to misleading results. 43 To this end, Ti mesh, as a low cost material ($.23/inch), was proven to be a suitable substrate due to its large-surface area, high stability in different pH values, and high corrosion resistance. 44 More importantly, Ti mesh showed very low activity toward water electrolysis.…”
Section: Introductionmentioning
confidence: 99%